CE: Centro de Educação - Borges Corte, Viviana; Artem dos Santos, Ana Julia; Guimarães Saraiva, Fernanda; Silva Clarindo Torteloti, Simone; Garcez Moura, Paulo Rogerio; de Araujo, Débora Cristina; Martins Lopes, Felipe; Gonçalves França, Marileide; Amorim Alves, Lucas; Sacht Góes, Margarete; Cecile Santana, Maria Gabriele (Guará Journal, 2023)
Resumos dos projetos do Centro de Educação